Proposal for Increase of Burglar Resistance of Commercially Manufactured Motor Vehicle Doors - Kamil Boc; Dagmar Vidrikova; Zoran Cekerevac; Jan Misik (Communications - Scientific letters of the University of Zilina, 2015)
In many cases the level of personal protection especially during transportation by personal motor vehicles is dependent on burglar resistance of used car body materials. Currently commercially manufactured personal motor vehicles are modified by insertion offiller materials of high density (steel plates inserted into doors, steel reinforcements of vehicle floors). This approach causes not only increase in financial costs for procurement of such modified (armoured) vehicle, but also changes its driving characteristics. Particularly its financial cost affects its accessibility to wide public. Several cases of use of small firearms against the occupants of commercially manufactured personal motor vehicles have been investigated in recent years. The results of such attacks were casualties or grievous bodily harm. Considered materials were experimentally tested for the purpose of increasing burglar resistance mainly of commercially manufactured motor vehicle doors and increase of their burglar resistance against shots from small firearms. The result of experiments that were carried out was the recommendation for reinforcement of car body doors of personal motor vehicles using molten polycarbonate materials. The thickness of 24 mm resulted in such increase of door burglar resistance that used small firearm ammunition could not penetrate this barrier.